The Effects of Influencer Credibility on Brand Attitude and Purchase Intention: The Moderating Role of Brand Congruence in Food Vlogger Marketing - Budhi Haryanto; Cheryl Marlitta Stefia; Sabda Aji Kurniawan; Andreas Ari Sukoco; Rohwiyati Rohwiyati (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2026)
Influencer marketing has become increasingly important in shaping consumer responses; however, limited understanding remains regarding the conditions under which influencer credibility is more strongly associated with brand evaluations and purchase intentions, particularly in food-vlogger marketing. This study examines the relationships among influencer credibility, brand attitude, and purchase intention and investigates brand congruence as a moderating boundary condition in the Indonesian culinary context. Using a cross-sectional survey, data were collected from 150 consumers familiar with Nex Carlos and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that influencer credibility is positively associated with brand attitude and purchase intention, while brand attitude is positively related to purchase intention. Brand congruence significantly strengthens all three relationships, demonstrating that endorsement effectiveness varies according to perceived influencer–brand compatibility. At the dimensional level, trustworthiness and expertise exhibit stronger contributions to influencer credibility than attractiveness. Theoretically, this study integrates Meaning Transfer Theory, Source Credibility Theory, and the Match-Up Hypothesis by conceptualizing brand congruence as a boundary condition, thereby extending meaning transfer toward a conditional explanation of endorsement effectiveness. Managerially, the findings highlight the importance of selecting credible influencers whose expertise, identity, audience, and communication style align with endorsed brands.